Synaptic remodeling follows upper motor neuron hyperexcitability in a rodent model of TDP-43 - Dyer, Marcus S.; Odierna, G. Lorenzo; Clark, Rosemary M.; Woodhouse, Adele; Blizzard, Catherine A. (Frontiers in Cellular Neuroscience, 2023)
Amyotrophic Lateral Sclerosis (ALS) is an incurable disease characterized by relentlessly progressive degeneration of the corticomotor system. Cortical hyperexcitability has been identified as an early pre-symptomatic biomarker of ALS. This suggests that hyperexcitability occurs upstream in the ALS pathological cascade and may even be part of the mechanism that drives development of symptoms or loss of motor neurons in the spinal cord. However, many studies also indicate a loss to the synaptic machinery that mediates synaptic input which raises the question of which is the driver of disease, and which is a homeostatic response. Herein, we used an inducible mouse model of TDP-43 mediated ALS that permits for the construction of detailed phenotypic timelines. Our work comprehensively describes the relationship between intrinsic hyperexcitability and altered synaptic input onto motor cortical layer 5 pyramidal neurons over time. As a result, we have constructed the most complete timeline of electrophysiological changes following induction of TDP-43 dysfunction in the motor cortex. We report that intrinsic hyperexcitability of layer 5 pyramidal neurons precedes changes to excitatory synaptic connections, which manifest as an overall loss of inputs onto layer 5 pyramidal neurons. This finding highlights the importance of hyperexcitability as a primary mechanism of ALS and re-contextualizes synaptic changes as possibly representing secondary adaptive responses. Recognition of the relationship between intrinsic hyperexcitability and reduced excitatory synaptic input has important implications for the development of useful therapies against ALS. Novel strategies will need to be developed that target neuronal output by managing excitability against synapses separately.